A precollege engineering program’s effects on the grade eight minority students’ attitudes and achievement in science and mathematics - Rosales, Ava Dawn Innerarity (Curtin University, 2009)
The National Science Board has declared that the production of citizens literate in science, technology, engineering and mathematics (STEM) is at an all time low in the United States. Schools are not sufficiently preparing students to enter and complete postsecondary studies in STEM areas to ensure their global competitiveness and place the economy in the stable standing experienced over the decades The U.S. has been known for its innovation; however, in the changing global climate, countries like India and China are out-producing, out-graduating and becoming the technological centres of the 21st Century. Thirty-five years ago, several organizations tried to address similar issues while focusing on minorities. Nevertheless, these efforts had not seemed to take a stronghold in school districts until recently, and even then, the question remains - What impact is the program having on eliminating the achievement gap so that all students are prepared to enter postsecondary studies in STEM?This research attempts to examine a precollege engineering program’s impact on minority students’ attitudes and achievement in mathematics and science. The program is called SECME, formerly the Southeastern Consortium for Minorities in Engineering. The study used a research framework for curriculum evaluation to assess the presence and participation of middle school minority students in a precollege engineering program through an analysis of the intent of the program, its implementation and the actual program outcomes. The research incorporated a prepost design with triangulation of methods through the use of pre- and posttest surveys using the modified Test of Science Related Attitudes (TOSRA) and Test of Mathematics Related Attitudes (TOMRA), researcher-developed questionnaires, and observations. Academic achievement was determined by student performance on the state administered Florida Comprehensive Assessment Test (FCAT).The setting of the study took place in an urban public school district, the fourth largest in the nation, located in the southeast section of the United States of America (USA). In this district, the minority group actually represented the majority of the district population; a demographic trend that is expected to be realised nationally in the next 50 years. The study took place over a two-year period and only sampled students from heterogeneously-mixed or co-educational middle school environments. However, due to problems with collecting post-test data, only the second year of the data are reported in this thesis. The participants in this study were from 10 of the 54 middle schools in the district. In-depth case studies were conducted with three of the schools which were purposefully selected for their diverse representations of student populations across the district.The modified TOSRA and TOMRA were used, along with researcher developed questionnaires, to analyse SECME and non-SECME middle grades students’ attitudes towards science and mathematics, respectively. The criterion-referenced test that held schools accountable for instruction, the Florida Comprehensive Assessment Test (FCAT) Sunshine State Standards (SSS), along with the FCAT Norm-Referenced Test (NRT) were used to ascertain and compare student achievement in science and mathematics, respectively. The FCAT SSS assesses the state standards that are expected to be taught in Florida science classrooms, and the FCAT NRT compares Florida students with their peers nationally. An analysis of these data indicated that a comparison in science achievement and attitudes to science between ethnicities for SECME and non-SECME students indicated no significant difference on the subscale posttest attitudinal scores. There were, however, significant differences for the non-SECME students between ethnicities and their scores on the FCAT SSS, in particular between White American and African American and between Others and African American students.In mathematics, there was a significant difference with respect to the FCAT SSS Mathematics and Achievement Levels, in favour of non-SECME students. Of note, there were no significant differences in the NRT Mathematics percentile and posttest attitudinal scores of the TOMRA for SECME and non-SECME males. This is of particular interest because the NRT compares students nationally as opposed to the FCAT SSS that assesses the student’s knowledge solely of the state’s curriculum content. Overall analysis, also indicated no statistically significant differences between ethnicities for the SECME students on the TOMRA scales or the Mathematics Achievement tests as opposed to the non-SECME students that demonstrated a statistically significant difference between ethnicities. This finding appears to be an indication that the achievement gap across ethnicities in this sample of SECME students did not exist. Another finding of interest was that Adoption of Scientific Attitude is a significant, independent predictor of FCAT Mathematics Achievement Level, and for SECME students, Enjoyment of Mathematics Lessons correlated positively with FCAT SSS Mathematics scores and FCAT NRT Mathematics percentile scores.The implementation of the program seems to be addressing the needs of minority participation with respect to Hispanic males, but insufficiently for the African American males and females. This finding was evident with the number of respondents on the surveys and participation in SECME program offerings and in the case studies. Qualitative data revealed that there is a lack of African American male coordinators and role models for the students participating in the SECME program which could result in fewer numbers of these students participating in events. There was also commentary that transportation was an issue for these students which may have contributed to the low participation of these students in Saturday seminars.A more extensive representation of the SECME program’s achieved curriculum would have been better analysed without certain limitations to the study. One such limitation was the fact that the FCAT SSS and NRT for science were only administered in the middle school years during grade 8. This limited the study sample for the quantitative data collection. Additionally, a longitudinal study of these same students as they move through senior high school, college, and eventually careers, should be forefront for further research to assess the efficacy of this and any other precollege engineering program.